Long-term progression-free survival of patients with metastatic melanoma or renal cell carcinoma following high-dose interleukin-2. (4th February 2021) - Clark, Joseph I; Curti, Brendan; Davis, Elizabeth J; Kaufman, Howard; Amin, Asim; Alva, Ajjai; Logan, Theodore F; Hauke, Ralph; Miletello, Gerald P; Vaishampayan, Ulka; Johnson, Douglas B; White, Richard L; et al.
Abstract : High-dose interleukin-2 (HD IL-2) was approved in the 1990s after demonstrating durable complete responses (CRs) in some patients with metastatic melanoma (mM) and metastatic renal cell carcinoma (mRCC). Patients who achieve this level of disease control have also demonstrated improved survival compared with patients who progress, but limited data are available describing the long-term course. The aim of this study was to better characterize long-term survival following successful HD IL-2 treatment in patients with no subsequent systemic therapy. Eleven HD IL-2 treatment centers identified patients with survival ≥5 years after HD IL-2, with no subsequent systemic therapy. Survival was evaluated from the date of IL-2 treatment to June 2017. Treatment courses consisted of 2 1-week cycles of HD IL-2. Patients were treated with HD IL-2 alone, or HD IL-2 followed by local therapy to achieve maximal response. 100 patients are reported: 54 patients with mM and 46 patients with mRCC. Progression-free survival (PFS) after HD IL-2 ranges from 5+ years to 30+ years, with a median follow-up of 10+ years. 27 mRCC and 32 mM are alive ≥10 years after IL-2. Thus, a small subset of patients with mM and mRCC achieve long-term PFS (≥5 years) after treatment with HD IL-2 as their only systemic therapy. The ability of HD IL-2 therapy to induce prolonged PFS should be a major consideration in studies of new immunotherapy combinations for mM and mRCC.